The Hand That Rocks the Cradle Nurturing Exclusivist Interpretations of Islam in the Malaysian Home. - Rahman, Serina (ISEAS - Yusof Ishak Institute, 2020)
As an increasingly conservative wave of Islam engulfs the globe, literalist Salafi interpretations of the faith have become prevalent in Malaysia. While there are several Islamic schools of thought in the country, including those deemed ""deviant"", the loudest voices are always the more extreme.Over the past year, there has been increasing recognition of women's roles as recruiters, financiers and influencers for radical Islamic groups. More women have been arrested for their support for and involvement in the Islamic State (IS), but much of the focus has been on their desire to marry a jihad.